Geração de cDNAs, primers e caracterização estrutural do tegumento de sementes de soja - Miranda, Helen Lúcia da Cruz (2008)
Soybean is one of the main world commodities and the seed is the key for high yields in this culture. Nevertheless, the soybean seed coat is the main modulator of seed quality, so, in this structure we could find answers for high seed quality production. The study goal is to identify structural contrasting traits, to obtain cDNA and to draw primers related to lignin synthesis and wax deposition in seed coat from two soybean genotypes. Plants were grown in greenhouse, flowers were identified and dated to follow the development after flowering until legumes were harvested (25, 30, 35, 40, 45, 50, 55 and 60 days). Seed coats were then analyzed in electronic microscopy and used to build a soybean seed coat cDNA library for permeability traits (lignin synthesis and wax deposition). In silico, analyzes were performed to obtain specific primers to detect soybean seed coat lignin and wax biosynthesis genes. According to the seed coat traits, we identified differences in the palisade cell thickness between genotypes. The protocol based on litio chloride was efficient to extract total RNA from both genotypes in all phases. The unidirectional cDNA multiplication was efficient for the generation of enough cDNA quantity for future projects. In silico analyzes allowed the development of 16 primers related to lignin and wax deposition biosynthesis in soybean seed coat.